1992
DOI: 10.1021/jf00017a003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat and proteolysis on deamidation of food proteins using peptidoglutaminase

Abstract: Enzymatic methods were developed for the deamidation of food proteins. Modification of proteins by peptidoglutaminase was dependent on their size and conformation. After such treatments as heat or alkali solubilization, which might have partially broken hydrogen and disulfide bonds, peptidoglutaminase deamidation of proteins increased by proteolysis as a function of percent peptide bond hydrolysis (DH), up to 54-fold at 20% DH. With prior heat treatment at 100 °C for 15 min, followed by proteolysis and alkali … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 12 publications
2
27
0
1
Order By: Relevance
“…Gill et al (8) reported that peptidoglutaminases are not active against caseins and whey proteins even after denaturation and are only active against glutaminyl residues in peptides with a molecular weight below 5,000. Hamada (9) reported slight enhancements of peptidoglutaminase-catalyzed protein deamidation using heat-and/or alkaline-treated proteins, but the degrees of deamidation were very low (0.8 to 3.0% for caseins) compared to those for the preparations treated by the combinations with proteolysis (ca. 38%).…”
Section: Discussionmentioning
confidence: 98%
“…Gill et al (8) reported that peptidoglutaminases are not active against caseins and whey proteins even after denaturation and are only active against glutaminyl residues in peptides with a molecular weight below 5,000. Hamada (9) reported slight enhancements of peptidoglutaminase-catalyzed protein deamidation using heat-and/or alkaline-treated proteins, but the degrees of deamidation were very low (0.8 to 3.0% for caseins) compared to those for the preparations treated by the combinations with proteolysis (ca. 38%).…”
Section: Discussionmentioning
confidence: 98%
“…Enzymatic methods using transglutaminase (TG) (Motoki, Seguro, Nio, & Takinami, 1986;Nonaka, Sawa, Matsuura, Motoki, & Nio, 1996;Ohtsuka, Umezawa, Nio, & Kubota, 2006), peptide-glutaminase (Hamada & Marshall, 1989, 1992, a combination of pH and protease (Matsudomi, Tanaka, Kato, & Kobayashi, 1986) and protein-glutaminase (PG) are known to be useful for the deamidation of food proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Hamada and Marshall (1992) reported that heat and proteolysis in casein deamidation using peptide-glutaminase and partial protein hydrolysis prior to enzymatic treatment increase the deamidation of casein amide residues. Previous research on the basic characteristics of PG has demonstrated that alpha-and beta-casein are excellent substrates of PG , and Gu et al (2001) reported that the molten globule state of alpha-lactalbumin, a milk whey proteins, affects the reactivity of PG.…”
Section: Introductionmentioning
confidence: 99%
“…Deamidation of proteins can improve their solubility, emulsifying activity, foaming activity, and other functional properties by increasing the number of negative charges and changing the overall structure (9). The chemical methods for protein deamidation, which include acid treatment, anion-catalyzed deamidation, dry heating under alkaline conditions, and thermal treatment, all cause collateral peptide bond cleavages (10,11).…”
mentioning
confidence: 99%